2019
DOI: 10.1002/dev.21911
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic characteristics of second‐order motor planning and performance in 6‐ and 10‐year‐old children and adults: Effects of age and task constraints

Abstract: This study explored age‐related differences in motor planning as expressed in arm‐hand kinematics during a sequential peg moving task with varying demands on goal insertion complexity (second‐order planning). The peg was a vertical cylinder with either a circular or semicircular base. The task was to transport the peg between two positions and rotate it various amounts horizontally before fitting into its final position. The amount of rotation required was either 0°, 90°, 180°, or −90°. The reaching for the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 36 publications
3
7
0
Order By: Relevance
“…Motor planning is defined as the ability to organize motor behavior to accomplish an anticipated goal-directed action. By definition motor planning processes depend on goal proximity: To adjust motor behavior to an imminent goal is referred to as first-order motor planning, whereas adjusting to subsequent goals is referred to as second-order motor planning (Rosenbaum et al, 2012 ; Domellöf et al, 2020 ). In tasks assessing motor planning, participants are required to first plan and then execute a motor sequence, during which the motor system needs to be controlled and can be adjusted.…”
Section: Embodied Planning: Integrating Theoretical and Methodological Approachesmentioning
confidence: 99%
See 2 more Smart Citations
“…Motor planning is defined as the ability to organize motor behavior to accomplish an anticipated goal-directed action. By definition motor planning processes depend on goal proximity: To adjust motor behavior to an imminent goal is referred to as first-order motor planning, whereas adjusting to subsequent goals is referred to as second-order motor planning (Rosenbaum et al, 2012 ; Domellöf et al, 2020 ). In tasks assessing motor planning, participants are required to first plan and then execute a motor sequence, during which the motor system needs to be controlled and can be adjusted.…”
Section: Embodied Planning: Integrating Theoretical and Methodological Approachesmentioning
confidence: 99%
“…During task execution, movement trajectories in 3D space can be captured (i.e., kinematics, see Figure 1 ). Although developmental studies exist that analyzed children's kinematics and response times (Domellöf et al, 2020 ), only a few combined the measures to explore the interaction between motor and cognitive skills (for an exception, see Gottwald et al, 2016 ). Domellöf et al ( 2020 ) analyzed age-related differences in the spatiotemporal segmentation of the movement path for the wrist, index finger, and object during a peg fitting task.…”
Section: Embodied Planning: Integrating Theoretical and Methodological Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…A skilled planner will take anticipatory actions to build the plan before acting. Anticipatory actions have been seen in both theoretical cognitive planning tasks (Davies, 2005) and motor planning tasks (Domellöf et al, 2020). Davies (2005) discussed the published literature on the role of expert knowledge in relation to the adoption of different planning strategies and Gilhooly (2005) discussed the literature on differences in planning by expert and novice chess players.…”
Section: Planningmentioning
confidence: 99%
“…Davies (2005) discussed the published literature on the role of expert knowledge in relation to the adoption of different planning strategies and Gilhooly (2005) discussed the literature on differences in planning by expert and novice chess players. Domellöf et al (2020), compared motor planning in children and adults and found that both adults and children were able to complete the task of grasping, transporting, and rotating pegs. However, the adults rotated the peg during transport while the children did so mostly after reaching the goal, meaning that the adults made an anticipatory action before encountering the issue at hand.…”
Section: Planningmentioning
confidence: 99%